Priority Selection of Fiohl (Fault Indicator Over Head Line) Installation Location Using the Entropy Method - Promethee - Akhmad Budianto; Udisubakti Ciptomulyono (Publikasi Indonesia, 2025)
The main challenge in electricity distribution in Riau and Riau Islands is the high incidence of power line faults. One effort to reduce power line faults is through the installation of FIOHL (Fault Indicator Overhead Line). FIOHL is a device used to detect faults on power lines, which can help quickly identify the location of the fault. In this study, PLN UP2D Riau plans to install 35 FIOHL units on 198 power lines. The objective of this study is to determine the priority order of power lines as the location for installing FIOHLs accurately. By using the Entropy method as a criterion weighting method and PROMETHEE (Preference Ranking Organisation Method for Enrichment Evaluations), the priority order of alternative solutions for determining the power lines can be obtained. The installation of FIOHL must meet eight criteria: number of outages, outage duration, Energy Not Served (ENS), number of outages without cause, feeder load, network length, number of customers, and keypoint ratio for each feeder. The number of customers has the highest weight at 0.175, followed by network length at 0.152 and ENS at 0.151. The priority locations for FIOHL installation using the PROMETHEE method show that the Maroko feeder ranks first with Phi = 0.6329, followed by the Laos feeder with Phi = 0.6247. The allocation of FIOHL installations across each Implementation Unit (UP3) includes 14 units for UP3 Bangkinang, 14 units for UP3 Dumai, 4 units for Pekanbaru, and 3 units for UP3 Rengat..